2019
DOI: 10.1002/bit.27208
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness affects the morphology and gene expression of epidermal neural crest stem cells in a short term culture

Abstract: According to the intrinsic plasticity of stem cells, controlling their fate is a critical issue in cell‐based therapies. Recently, a growing body of evidence has suggested that substrate stiffness can affect the fate decisions of various stem cells. Epidermal neural crest stem cells as one of the main neural crest cell derivatives hold great promise for cell therapies due to presenting a high level of plasticity. This study was conducted to define the influence of substrate stiffness on the lineage commitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Moreover, Nestin positive cells decreased over time for all cell lines except for hNSC#1: this is likely ascribable to an initially higher proliferation rate (until 1WIV) caused by an enriched percentage of stem/progenitor cells population that progressively faded into differentiating (or fate-committed) cells ( Figure 4G). To note, the obtained values can be easily modified with further customizations of HYDROSAP depending on the regenerative application: indeed we already demonstrated that by tuning different key experimental parameters (e.g., matrix stiffness, presence of functional motifs, and/or addition of neurotrophic factors) it is possible to modulate NSCs differentiation and improve differentiation toward neuronal fate (Jain et al, 2020): for example, we showed that increments of cell proliferation rate and neuronal differentiation is inversely proportional to the matrix stiffness, while stiffness and astrocytes number directly correlated (Cunha et al, 2011;Caprini et al, 2013;Han et al, 2020;Pandamooz et al, 2020). In future experiments, it will also be interesting to assess the influence of time-evolving viscoelastic properties of hydrogels over cellular behavior (Mattei et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, Nestin positive cells decreased over time for all cell lines except for hNSC#1: this is likely ascribable to an initially higher proliferation rate (until 1WIV) caused by an enriched percentage of stem/progenitor cells population that progressively faded into differentiating (or fate-committed) cells ( Figure 4G). To note, the obtained values can be easily modified with further customizations of HYDROSAP depending on the regenerative application: indeed we already demonstrated that by tuning different key experimental parameters (e.g., matrix stiffness, presence of functional motifs, and/or addition of neurotrophic factors) it is possible to modulate NSCs differentiation and improve differentiation toward neuronal fate (Jain et al, 2020): for example, we showed that increments of cell proliferation rate and neuronal differentiation is inversely proportional to the matrix stiffness, while stiffness and astrocytes number directly correlated (Cunha et al, 2011;Caprini et al, 2013;Han et al, 2020;Pandamooz et al, 2020). In future experiments, it will also be interesting to assess the influence of time-evolving viscoelastic properties of hydrogels over cellular behavior (Mattei et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…This advantage over BM-MSCs supports the application of these stem cells to elderly individuals, who have an increased incidence of stroke. According to accumulating evidence, EPI-NCSCs express several trophic factors, which their rate of expression can be manipulated through the use of different preconditioning strategies [125][126][127][128][129] to achieve optimum efficiency after transplantation. In addition, administration of EPI-NCSCs via intra-arterial or intra venous routes following reperfusion, created a comparable outcome to intra-arterial grafted BM-MSCs, 7 days after cerebral ischemia [37].…”
Section: Epidermal Neural Crest Stem Cells As a Promising Candidate In Strokementioning
confidence: 99%
“…This advantage over BM-MSCs supports the application of these stem cells to elderly individuals, who have an increased incidence of stroke. According to accumulating evidence, EPI-NCSCs express several trophic factors, which their rate of expression can be manipulated through the use of different chemical agents [119][120][121][122] to achieve optimum efficiency after transplantation. In addition, administration of EPI-NCSCs via intra-arterial or intra venous routes following reperfusion, created a comparable outcome to intra-arterial grafted BM-MSCs, 7 days after cerebral ischemia [34].…”
Section: Epidermal Neural Crest Stem Cells As a Promising Candidate Imentioning
confidence: 99%